CHEMICAL COMPOSITION OF MODERN AND TRADITIONALLY PROCESSED SAUSAGES - A. A. Khadija, Osman; M. Nabiela, El Bagir (Journal of Veterinary Medicine and Animal Production, 2022)
This study was conducted to compare the chemical composition of sausage samples from two local modern processing plants and a third traditionally prepared samples as control.All samples purchased from Omdurman market ,Khartoum State, Sudan. A proximate analysis was measured for the three samples of the sausages as moisture, crude protein , total lipids and cholesterol content. . The statistical analysis of the data revealed clear differences between n the two modern processed samples and traditionally processed one. A significant (P < 0.001) high moisture content in traditionally made sausage was observed compared to the two modern processed sausage samples. Also the study showed significantly (P< 0.05) higher level of total lipids in one of the modern processed samples compared to the traditionally processed sausage. No significant differences were recorded for the contents of crude protein and cholesterol within all types of sausages. The study showed significant differences in water and fat contents, within the modern processed sausages, which was suggested to be due to the addition of expanders in the modern plants. These findings implied that further extensive studies are needed to show the actual differences in the composition of fats or proteins in modern processed sausages. This can evaluate their nutritional values and show how modern processed sausages, in Sudan, can be ranked as healthy food.